Development of a high‐resolution confocal micro‐XRF instrument equipped with a vacuum chamber. (17th April 2013) - Nakazawa, Takashi; Tsuji, Kouichi
Abstract : A confocal micro‐X‐ray fluorescence (micro‐XRF) instrument equipped with a vacuum chamber was newly developed. The instrument is operated under a vacuum condition to reduce the absorption of XRF in the atmosphere. Thin metal layers were developed to evaluate the confocal volume, corresponding to depth resolution. A set of thin metal layers (Al, Ti, Cr, Fe, Ni, Cu, Zr, Mo, and Au) was prepared by a magnetron sputtering technique. The depth resolutions of the new instrument were varied from 56.0 to 10.9 µm for an energy range from 1.4 to 17.4 keV, respectively. The lower limit of detection (LLD) was estimated by comparison with a glass standard reference material NIST SRM 621). The LLDs obtained by a conventional micro‐XRF were compared with the LLDs obtained by a confocal micro‐XRF instrument. The LLDs were improved in the measurement under confocal configuration because of the reduction of background intensity. Finally, layered materials related to forensic investigation were measured. The confocal micro‐XRF instrument was able to nondestructively obtain the distribution of light elements that cannot be detected by measurement in air. Copyright © 2013 John Wiley & Sons, Ltd.